Energy Geotechnics SEG-2018 - Ferrari, Alessio; Laloui, Lyesse (Springer Series in Geomechanics and Geoengineering,, 2019)
This book collects selected full papers presented at the International Symposium on Energy Geotechnics 2018 (SEG-2018), held on 25th - 28th September 2018, at the Swiss Federal Institute of Technology in Lausanne (EPFL). It covers a wide range of topics in energy geotechnics, including energy geostructures, energy geostorage, thermo-hydro-chemo-mechanical behaviour of geomaterials, unconventional resources, hydraulic stimulation, induced seismicity, CO2 geological storage, and nuclear waste disposal as well as topics such as tower and offshore foundations. The book is intended for postgraduate students, researchers and practitioners working on geomechanics and geotechnical engineering for energy-related applications.